On geodesic semi strongly E-convex functions - Kilicman, Adem; Saleh, Wedad (Taylor & Francis, 2016)
In this article, a new class of function called geodesic semi strongly E-convex functions and generalized geodesic semi strongly E-convex functions are introduced. Also, some of their properties are obtained.